2016
DOI: 10.1002/biot.201500049
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles concentration is a promising and important parameter for industrial bioprocess monitoring

Abstract: Extracellular vesicles (EVs) are membrane vesicles that are produced by cells to be released into their microenvironment. In this study, we present the EV concentration as a new factor for optimization of industrial bioprocess control. The release of EVs depends on many cell properties, including cell activation and stress status, and cell death. Therefore, the EV concentration might provide a readout for identification of the cell state and the conditions during a bioprocess. Our data show that the EV concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The only studies conducted yet on the matter of CHO exosomes claimed an increased growth (Takagi et al 2020) and attenuated apoptosis mediated by exosomes (Han and Rhee 2018). Others suggest exosomes as potential parameter for industrial bioprocess monitoring (Zavec et al 2016). Moreover, exosomes are considered potential drug delivery vehicle, due to their specific tropism, proposedly weak immunogenicity and the ability to cross the blood-brain-barrier (Liu and Su 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The only studies conducted yet on the matter of CHO exosomes claimed an increased growth (Takagi et al 2020) and attenuated apoptosis mediated by exosomes (Han and Rhee 2018). Others suggest exosomes as potential parameter for industrial bioprocess monitoring (Zavec et al 2016). Moreover, exosomes are considered potential drug delivery vehicle, due to their specific tropism, proposedly weak immunogenicity and the ability to cross the blood-brain-barrier (Liu and Su 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that virus like particles and viruses may be contaminated with exosomes and other extracellular particles . Even they can be used for bioprocess monitoring, because the exosome content reflects the metabolic state of the cells . Exosome research is one of the hottest topics in life science and biopharmaceutical development and is very promising because with exosomes we may really interfere with cell communication and specifically transmit information into micro environment of cells …”
mentioning
confidence: 99%
“…The practical implications of this study are twofold. Differential miR and protein cargo loading suggest a use for CHO EVs as a culture diagnostic tool; indeed, the use of EV concentration as a metric for CHO culture health has already been demonstrated (Zavec et al, 2016). Both RT‐PCR and our Qubit (total miR) and Bradford protein assays provide proof‐of‐concept for the relatively quick and simple evaluation of EV cargo.…”
Section: Discussionmentioning
confidence: 99%